2001
DOI: 10.1037/0021-843x.110.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Is smoking automatic? Demands of smoking behavior on attentional resources.

Abstract: The role of attention in the production of smoking behavior was investigated. Experienced and novice smokers were asked to perform a reaction time (RT) task under 4 conditions: while smoking (smoking), while mimicking all aspects of smoking except inhaling (pseudosmoking), while simply holding a cigarette (holding), and while not smoking (baseline). Experienced smokers' RTs increased during the pseudosmoking and holding conditions compared with baseline but did not differ between the smoking and baseline condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
39
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 39 publications
12
39
0
Order By: Relevance
“…Our results also align well with the broader literature demonstrating detrimental effects on cognition caused by dual-task performance (e.g., Baxter & Hinson, 2001;CepedaBenito & Tiffany, 1996) and the exertion of self-control . It may be fruitful for future research to further examine parallels between these domains.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our results also align well with the broader literature demonstrating detrimental effects on cognition caused by dual-task performance (e.g., Baxter & Hinson, 2001;CepedaBenito & Tiffany, 1996) and the exertion of self-control . It may be fruitful for future research to further examine parallels between these domains.…”
Section: Discussionsupporting
confidence: 80%
“…Zuj et al 4 task performance (Cepeda-Benito & Tiffany, 1996), in which a person is required to perform a task while concurrently performing a second task. This necessitates allocating some resources to the second task, which leaves fewer resources available to direct toward the first task, resulting in effects such as increased reaction time on the first task (Baxter & Hinson, 2001;Cepeda-Benito & Tiffany, 1996). Applied to (cigarette) cravings, these findings indicate that attentional resources are directed towards suppressing automatic smoking behaviors, leaving fewer resources for the current task.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The basket contained two minisized bars of each of eight popular chocolates: Mars, Snickers, Cherry Ripe, Crunchie, Timeout, Flake, Picnic and Twix. As evidence concerning cigarette cravings indicates that cue exposure is maximally effective if the participant interacts with the craving induction stimulus (Baxter & Hinson, 2001), participants were instructed to actively engage with the chocolate. Specifically, they were asked to choose their favourite chocolate bar, to unwrap it, and then to place the wrapper and the chocolate bar on a tray on top of the computer hard drive.…”
Section: Methodsmentioning
confidence: 99%
“…These schemata can be triggered rapidly by smoking cues, thus increasing the probability that smokers will perform substance-use actions independently of intentional processes. It has been shown that smoking behavior becomes automatized in frequent smokers (Baxter and Hinson, 2001;Field et al, 2006). Furthermore, recent synaptic plasticity research has identified the dorsal striatum as the region contributing to the establishment of persistent drugrelated habits (Gerdeman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%